Civilisation and Dialogue - Gunn, Alastair S. (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
For the first time in human history, civilisations, cultures, and communities are compelled to relate to one other on a constant and continuous basis. Yet mutual ignorance exacerbated by mutual suspicion and hostility inhibit them from establishing ties that endure and flourish. Sometimes hostility erupts into bloody conflicts … indeed, communal violence has become the bane of mankind.. Dialogue and mutual understanding are the prerequisites for building just and equitable relations between cultures and civilisations.